RANCANG BANGUN MEDIA PEMBELAJARAN PEMROGRAMAN DASAR BERBASIS ANDROID - Resi Maielfia; Titi Sriwayuni (Universitas Negeri Padang, 2019)
The design of the media explains about a learning medium that is used by students to help in achieving learning objectives. The media created are basic programming learning media based on Android. Basic programming is a vocational subject for class X vocational students. This subject explains how to solve a problem logically and systematically in the form of a program. In this media there are learning materials, syllabus, lesson plans, learning videos and practice questions to find out students' understanding of the material presented. There is a help menu to assist users in running this learning media. Media that is designed based on Android uses the Java programming language with android Studio as the IDE and prototyping models for the development model. This learning media is expected to increase students' insights on learning Basic Programming. Keywords:Android, Media, Basic programming.RANCANG BANGUNMEDIA PEMBELAJARAN PEMROGRAMAN DASAR BERBASIS ANDROID